Stress analysis of four-story building to detect the crack location under the earthquake loading - Alfinna Mahya Ummati (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2022)
A 3D frame element modelling conducted in order to identify the crack location of the educational building on South Lampung City. Many cracking visually appeared in a building and many of leaking observed that the building performs an over displacement. This research proposed an analysis in order to detect the crack location due to the building’s overstressed before and under the certain earthquakes loading. First, the building subjected to the deadload and service loading and was found that the building in a health condition and there is no cracking identified. Second, an El-Centro earthquake normalized and fitted with the site location and loaded to the building. Under 200-gal earthquake which similar to MMI scale VI to VIII with the moderate damage that possibly occur in Lampung, the crack detected in all member of the building, either major or minor cracking. This research proposed the method which considerable to use in observing the cracking location, generally.